Nanomedicine in cancer therapy: promises and hurdles of polymeric nanoparticles - Carmen Paus; Robbert van der Voort; Alessandra Cambi (Open Exploration Publishing Inc., 2021)
The limitations of current cancer treatments have stimulated the application of nanotechnology to develop more effective and safer cancer therapies. Remarkable progress has been made in the development of nanomedicine to overcome issues associated with conventional cancer treatment, including low drug solubility, insufficient targeting, and drug resistance. The modulation of nanoparticles allows the improvement of drug pharmacokinetics, leading to improved targeting and reduced side effects. In addition, nanoparticles can be conjugated to ligands that specifically target cancer cells. Furthermore, strategies that exploit tumor characteristics to locally trigger drug release have shown to increase targeted drug delivery. However, although some clinical successes have been achieved, most nanomedicines fail to reach the clinic. Factors that hinder clinical translation vary from the complexity of design, incomplete understanding of biological mechanisms, and high demands during the manufacturing process. Clinical translation might be improved by combining knowledge from different disciplines such as cell biology, chemistry, and tumor pathophysiology. An increased understanding on how nanoparticle modifications affect biological systems is pivotal to improve design, eventually aiding development of more effective nanomedicines. This review summarizes the key successes that have been made in nanomedicine, including improved drug delivery and release by polymeric nanoparticles as well as the introduction of strategies that overcome drug resistance. In addition, the application of nanomedicine in immunotherapy is discussed, and several remaining challenges addressed.